Implementation of Theory of Planned Behavior on Behavior Change and Outcomes in Type 2 Diabetes Mellitus Patients in Surakarta, Central Java, Indonesia - Burhannudin Ichsan; Bhisma Murti; Revi Gama Hatta Novika (Journal of Epidemiology and Public Health, 2025)
Background: The Theory of Planned Behavior (TPB) can serve as a conceptual framework for improving healthy behaviors among patients with type 2 diabetes mellitus (T2DM). The application of TPB is essential for predicting both behavioral patterns and health outcomes in individuals with T2DM. This study aimed to assess the implementation of TPB on behavioral change and outcomes in T2DM patients Subjects and Method: This cross-sectional study was conducted in Surakarta, Indonesia. There was 200 type 2 DM patients selected by purposive sampling. The dependent variables were HbA1c and behavior. The independent variables were behavioral belief, outcome evaluation, normative belief, motivation, control belief, control power, attitude, subjective norm, perceived behavioral control, and intention.  Data were collected using a set of questionnaires and analyzed using path analysis. Results: HbA1c ≥6.5% was directly reduced by strong behavior, but it was statistically non significant (b= -0.22; 95%CI= -0.15 to 1.08; p= 0.745). Behavior was directly and significantly increased by strong intention (b= 1.66; 95% CI= 1.03 to 2.30; p<0.001) and high perceived behavior control (b= 0.87; 95% CI= 0.23 to 1.50; p= 0.007). Conclusion: The Theory of Planned Behavior can be used to predict healthy behavior among patients with type 2 DM.